Penerapan Pembelajaran Inkuiri Terbimbing dengan Pendekatan Concrete-Representational-Abstract Terhadap Adversity Quotient Siswa SMP - Afri, Lisa Dwi (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This research is motivated by the importance of developing students’s adversity quotient (AQ). This research examines the difference of students’s AQ in Guided Inquiry learning with Concrete-Representational-Abstract approach (ITCRA) and students’s AQ in conventional learning. This research is quasi experiment with nonequivalent control group design. The population is students which grade eighth in SMPN 1 Padang Panjang, and the samples is selected two classes from seven existing classes. Instruments used to collect data is scale of adversity quotient dan intervies guidelines. Data obtained were analyzed using mean difference t-test. The results show that there are differences of student’s AQ getting ITCRA learning and student’s AQ getting conventional learning.Keywords: Guided Inquiry, Concrete-Representational-Abstract, Adversity Quotient